Diskursus Model Kebijakan Pendidikan Islam Era Otonomi - Ahmad Ali Riyadi (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2018)
This study aims to examine the debate on concepts offered in the reform era marked by the collapse of the new order. At this time there has been a change in the system of authority of the political bureaucracy of Islamic education policy. This authority relates to changes in the authority to handle educational institutions submitted to the regions. Data collection in this study was carried out through literature studies. While the data analysis using content analysis method (Contents analysis) is a technique to draw conclusions by identifying the specific characteristics of a message in a subjective and systematic manner. The results of this study indicate that there are several models of education management that become policy discourses, including models of school-based education systems and competency systems. In the midst of the debate offered by Islamic education institutions it is still under the authority of the ministry of religion structurally but culturally Islamic education institutions follow a curriculum model that was developed in a decentralized manner.